1994
DOI: 10.1037/0003-066x.49.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Does psychiatric disorder predict violent crime among released jail detainees? A six-year longitudinal study.

Abstract: The authors examined whetherjail detainees with schizo phrenia. major affective disorders, alcohol or drug use disorders, or psychotic symptoms hallucinations and de lusions are arrested more oftenfor violent crimes six years after release than detainees with no disorders. Trained interviewers assessed 728 randomly selected malejail de tainees using the National Institute ofMental Health Di agnostic Interview Schedule and then obtainedfollow-up arrest data for six years. Neither severe mental disorder nor subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(40 citation statements)
references
References 46 publications
2
35
0
3
Order By: Relevance
“…Although this finding is in line with earlier studies in adult offenders, 5,6 more studies in detained juveniles are warranted before a firm conclusion can be drawn. For example, specific psychiatric disorders such as psychotic disorders occurred in low rates.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Although this finding is in line with earlier studies in adult offenders, 5,6 more studies in detained juveniles are warranted before a firm conclusion can be drawn. For example, specific psychiatric disorders such as psychotic disorders occurred in low rates.…”
Section: Discussionsupporting
confidence: 78%
“…In adult (forensic) psychiatry, studies have shown this is not the case. 5,6 Nevertheless, serious offenders in particular are often considered to be mentally ill, dangerous, and thus likely to reoffend. As no empirical evidence for such speculation is available, such stereotyping must critically be examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a handful of studies (21,(23)(24)(25)(26) have assessed recidivism among released inmates with mental illness, only one of these included an assessment of parole revocation (21). In a study of 72 Canadian parolees, Porporino and Motiuk (21) reported that compared with parolees without a major mental illness, parolees with such a condition were more likely to be reincarcerated for parole violations but less likely to be reincarcerated for committing a new criminal offense.…”
Section: Discussionmentioning
confidence: 99%
“…Madde ba¤›ml›lar›n›n, kulland›klar› madde etkisi alt›nda birçok riskli davran›fla ve suç ifllemeye daha yatk›n olduklar› bilinmektedir (25,26). Bu kiflilerin en çok madde bulundurmak ve satmak, madde elde etmek için h›r-s›zl›k, gasp gibi suçlara kar›flt›klar›, sürdürdükleri yaflam flekli nedeniyle suç iflleme potansiyeline sahip kiflilerle iliflki içinde olduklar› ve suç iflleyen ba¤›ml›lar›n birço-¤unun suç ifllemeden hemen önce veya ifllerken madde kulland›klar› da bildirilmektedir (27)(28)(29)(30).…”
Section: Gereç Ve Yöntemunclassified